A Combined Experimental and Theoretical Study of Lithiation Mechanism in ZnFe2O4 Anode Materials. (20th March 2018) - Wang, Lei; McCarthy, Alison; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.
ABSTRACT: ZnFe2 O4 (ZFO) represents a promising anode material for lithium ion batteries, but there is still a lack of deep understanding of the fundamental reduction mechanism associated with this material. In this paper, the complete visualization of reduction/oxidation products irrespective of their crystallinity was achieved experimentally through a compilation of in situ X-ray diffraction, synchrotron based powder diffraction, and ex-situ X-ray absorption fine structure data. Complementary theoretical modelling study further shed light upon the fundamental understanding of the lithiation mechanism, especially at the early stage from ZnFe2 O4 up to Lix ZnFe2 O4 (x = 2).